Immunotherapy-associated cardiovascular toxicities: insights from preclinical and clinical studies - Kong, Youqian; Wang, Xiaoyu; Qie, Rui (Frontiers in Oncology, 2024)
Immune checkpoint inhibitors (ICIs) have become a widely accepted and effective treatment for various types of solid tumors. Recent studies suggest that cardiovascular immune-related adverse events (irAEs) specifically have an incidence rate ranging from 1.14% to more than 5%. Myocarditis is the most common observed cardiovascular irAE. Others include arrhythmias, pericardial diseases, vasculitis, and a condition resembling takotsubo cardiomyopathy. Programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1) pathway, cytotoxic T-lymphocyte antigen-4 (CTLA-4) pathway, and the recently discovered lymphocyte-activation gene 3 (LAG-3) pathway, play a critical role in boosting the body’s natural immune response against cancer cells. While ICIs offer significant benefits in terms of augmenting immune function, they can also give rise to unwanted inflammatory side effects known as irAEs. The occurrence of irAEs can vary in severity, ranging from mild to severe, and can impact the overall clinical efficacy of these agents. This review aims to summarize the underlying mechanisms of cardiovascular irAE from both preclinical and clinical studies for a better understanding of cardiovascular irAE in clinical application.